Analysis of endothelial nitric oxide synthase (eNOS) G894T polymorphism and semen parameters in a Chinese Han population. (27th May 2013) - Yu, Q.; Zhang, Y.; Xia, Y.; Yang, X.; Li, N.; Ye, L.; Mao, X.
Summary Previous studies have shown that endothelial nitric oxide synthase (eNOS) gene may be involved in abnormal semen parameters. However, the relationship between eNOS G894T polymorphism and semen parameters remains controversial. The purpose of this study was to investigate the association of eNOS G894T polymorphism and semen parameters. The genotype frequency of eNOS G894T was determined in 270 idiopathic asthenozoospermia patients and 248 ethnically matched healthy volunteers using iPLEX genotyping assays on a MassARRAY® (Sequenom, San Diego, CA, USA) platform. The statistical analysis performed with Fisher's exact test showed no significant difference in frequencies of genotypes between both groups. The logistic regression showed that genotypes GT, TT and allele T were nonassociated with increased risk of asthenozoospermia in the patient group with ≤5% or >5% sperm with normal forms. The dependence on genotypes of semen parameters was further investigated in both patients and control group. There was no significant difference as compared to control group (P > 0.05). Our study indicated that eNOS gene G894T polymorphism may not have an adverse effect on semen parameters in a Chinese Han population.